MODERNIZATION OF ARABIC LANGUAGE LEARNING BASED ON Islamic Boarding School AT PERBOBUHAN KEBAJIKAAN AL-MUHIBBIN MALAKA MALAYSIA - M Aziz Mardinsyah; Tumiran (International Journal of Society and Law, 2024)
This study aims to examine the modernization of Islamic boarding school-based Arabic language learning in Al-Muhibbin Malaka Perbangunan Kebajikan, Malaysia. Attention and analysis of Arabic language learning remain important, even in the Islamic boarding school environment. However, this learning may still need improvement, considering that many Islamic boarding schools pay less attention to learning methods, even though this method is one of the important elements in developing learning, especially in Arabic language learning. This study is included in educational evaluation research with a focus on Arabic language teaching practices implemented in Perbangunan Kebajikan Al-Muhibbin Malaka, Malaysia.